2019
DOI: 10.3390/ani9090586
|View full text |Cite
|
Sign up to set email alerts
|

Threonine Requirements in Dietary Low Crude Protein for Laying Hens under High-Temperature Environmental Climate

Abstract: Simple SummaryThe threonine (Thr) requirement of laying hens in a high-temperature climate is scarcely referred in the review of literature. Therefore, our aim was to estimate the dietary Thr requirement in low CP diets in a high-temperature environmental climate. Based on our findings, the optimal dietary Thr requirements to optimize egg production, serum uric acid, and serum CuZn-SOD were 0.58%, 0.59%, and 0.56%, respectively, by regression analysis.AbstractLohmann Brown hens (n = 420), at 28 weeks of age, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…In agreement with the obtained findings from this study, Zhang et al (2020) In the present study, the serum level of UA was significantly higher in the HS group compared to the control group (Table 3; p < 0.05). UA is the end-metabolic product of protein metabolism in avian species and has been suggested as a potent scavenger of free radicals in broiler chickens (Azzam et al, 2019). Xie et al (2015) reported that the circulating level of UA increased in HS broilers and it could be utilized as a detectable indicator of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the obtained findings from this study, Zhang et al (2020) In the present study, the serum level of UA was significantly higher in the HS group compared to the control group (Table 3; p < 0.05). UA is the end-metabolic product of protein metabolism in avian species and has been suggested as a potent scavenger of free radicals in broiler chickens (Azzam et al, 2019). Xie et al (2015) reported that the circulating level of UA increased in HS broilers and it could be utilized as a detectable indicator of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the serum level of UA was significantly higher in the HS group compared to the control group (Table 3 ; p < 0.05). UA is the end‐metabolic product of protein metabolism in avian species and has been suggested as a potent scavenger of free radicals in broiler chickens (Azzam et al., 2019 ). Xie et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2013b) 24-40 Hy-Line W36 4.8 vs. 6.6 12.14 NS Cardoso et al. (2014a) 60 -76 DeKalb White Leghorn 5.2 vs. 6.2 11.72 108.2 vs. 110.1 Azzam et al. (2019) 28-40 Lohman brown 4.3 vs. 7.4 11.93 NS Abbreviation: NS, nonsignificant.…”
Section: Importance Of Dietary Amino Acids In Laying Hensmentioning
confidence: 99%
“…(2010) 54-58 Lohman brown LRP 131 50 508 505 Rocha et al. (2013b) 24-40 Hy-Line W36 Polynomial 142 523 523 606 Azzam et al. (2019) 28-40 Lohman brown Polynomial 140 708 Mean 41.9 133 500 469 Simple mean of total threonine recommendations based on FCR (SD = ±7.8) and egg mass (SD = ±6.3) is 457 ± 6.9 mg/g/bird.…”
Section: Importance Of Dietary Amino Acids In Laying Hensmentioning
confidence: 99%
“…There are several environmental factors that affect layer chickens in production, but the most debilitating is heat stress, which affects production parameters, especially for birds that are sensitive to heat waves because of their feather covering and lack of sweat glands, heat stress results in a higher incidence rate of oxidative stress in birds (Azzam et al, 2019;Khan et al, 2014). Heat stress may also increase mortality rate which leads to economic losses (Khan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%